The astounding broccoli boy - Cottrell Boyce, Frank (Walden Pond Press, an imprint of HarperCollinsPublishers, 2015)
Rory Rooney likes to be prepared for anything, but when he inexplicably turns green and finds himself in an experimental hospital ward with his nemesis, school bully Tommy-Lee "Grim" Komissky, everyone is baffled but Rory believes he and Grim have become superheroes.